CDM Potential of Dairy Sector in India - Axel Michaelowa; Smita Sirohi (Hamburg Institute of International Economics (HWWA), 2004)
Among the co-operative mechanisms established under the Kyoto Protocol, the Clean Development Mechanism is the only one, which has the potential to assist developing countries in achieving sustainable development by promoting environmentally friendly investment from industrialized country governments and businesses. Although, apart from nuclear energy and deforestation avoidance, all other projects are eligible under CDM, so far, the CDM projects have largely been confined to industrial sector and agricultural sector, in general has been left out. To assess the issues and opportunities presented by potential international markets for greenhouse gases offsets through the CDM and facilitate implementation of CDM in India, a National Startegy Study on CDM is already underway in the country. However, here again, the agriculture sector, in general, and livestock sector, in particular has not been included in the ambit of NSS, although in India total emissions of methane from livestock are highest. The present study is a pioneering attempt to examine the prospects of CDM projects in the Indian dairy sector. This report discusses the issues of baseline additionality and sustainable development in the context of CDM projects in the dairy sector in India, estimates the cost of various methane mitigation strategies in the sector and highlights the key constraints for the potential CDM projects in this sector.
Keywords: Q54; Q18; O13; 330; CDM; agriculture; dairy; India; Clean Development Mechanism; Milchviehhaltung; Klimaschutz; Indien